Turkey's patent market position in Europe - (:unkn) unknown (My University, 2006)
Patents are monopoly rights given to "new," "inventive, " and "industrially applicable" engineering ideas. Internationally recognized patent productivity is one of the strongest indicators of the technological development of a country. In this study, we explore the key performance characteristics of Turkey in European innovation market. Turkey became a member of European Patent Organization in 2000. During the ongoing integration process into the European Union, competition with other European countries is important, especially in cutting-edge technologies. The research reported on here partially involved gathering, organizing, and analyzing of innovation-related macro data of Turkey and definition of the country's position in the European patent market. In this paper, we discuss the following: a) competencies and difficulties of Turkish innovators; b) country performance compared with other European countries; and c) a roadmap for the development of innovation strategies of Turkey based on numerous suggestions. To make these statistical conclusions, we utilized raw data of annual reports of OECD, UNESCO, UN, World Bank, EU, WIPO, EPO, and TPE. (c) 2006 PICMET.